2004
DOI: 10.1002/anie.200353300
|View full text |Cite
|
Sign up to set email alerts
|

A General Soft‐Chemistry Route to Perovskites and Related Materials: Synthesis of BaTiO3, BaZrO3, and LiNbO3 Nanoparticles

Abstract: Perovskites and related compounds are one of the most widely investigated classes of materials in solid-state chemistry because of their ferroelectric properties, which find a wide variety of applications in nonlinear optics, thin-film capaci-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
178
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(184 citation statements)
references
References 21 publications
1
178
1
Order By: Relevance
“…Quite recently, Niederberger et al 41 reported similar results for LiNbO 3 prepared by a soft-chemistry route.…”
Section: Impedance Spectroscopymentioning
confidence: 69%
“…Quite recently, Niederberger et al 41 reported similar results for LiNbO 3 prepared by a soft-chemistry route.…”
Section: Impedance Spectroscopymentioning
confidence: 69%
“…Some groups have reported the possibility of synthesizing LNB nanoparticles by wet-chemical methods [5][6][7][8], but recently the possibility of achieving this goal by milling was also demonstrated [9], this method being cheaper and easier to transfer to industrial production than chemical synthesis. In this way, Fe-and Cu-doped nanoparticles with particle size in the range of 10-100 nm have been obtained, and fhey have been used to form stable suspensions in heptane, allowing the fabrication of new hybrid materials [9][10][11].…”
mentioning
confidence: 99%
“…Hydrothermal method is one of the most popular approaches to obtain the perovskite nanostructures directly from solution, but the synthesis process is often conducted at elevated temperature (typically 100-280 ℃) and/or under relatively high pressure to improve the crystallinity of the products. To further simplify the process and lower the processing temperature and pressure, several routs have been achieved [4][5][6][7][8][9][10][11][12]. Even more, perovskite structured nanocrystals with much complicated compositions have been developed based on above research works to develop new functional ceramics [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%